2012
DOI: 10.1016/j.chom.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Infection-Induced Intestinal Oxidative Stress Triggers Organ-to-Organ Immunological Communication in Drosophila

Abstract: Local infections can trigger immune responses in distant organs, and this interorgan immunological crosstalk helps maintain immune homeostasis. We find that enterobacterial infection or chemically and genetically stimulating reactive oxygen species (ROS)-induced stress responses in the Drosophila gut triggers global antimicrobial peptide (AMP) responses in the fat body, a major immune organ in flies. ROS stress induces nitric oxide (NO) production in the gut, which triggers production of the AMP Diptericin, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 28 publications
5
88
0
1
Order By: Relevance
“…The present study using Drosophila third instar larvae supports the scenario that Toll signaling is a key mechanism in the host defense system that responds to endogenous inflammatory factors, consistent with the dedicated role of Toll-like receptors in vertebrate "danger" sensing (1,47,48). A number of previous studies that focused on nonmicrobial signal-activated host defense in Drosophila showed that the Imd/Relish cascade is activated by endogenous inflammatory agents, such as undigested DNA (49,50) and the neuro-peptide bursicon (51), as well as undefined humoral factors released from the intestine after tissue damage (52). The observation of different signaling pathways that are activated in response to various forms of stress, and in the dronc mutant, indicate that specific detection mechanisms are used to discriminate among various forms of threat.…”
Section: Discussionsupporting
confidence: 52%
“…The present study using Drosophila third instar larvae supports the scenario that Toll signaling is a key mechanism in the host defense system that responds to endogenous inflammatory factors, consistent with the dedicated role of Toll-like receptors in vertebrate "danger" sensing (1,47,48). A number of previous studies that focused on nonmicrobial signal-activated host defense in Drosophila showed that the Imd/Relish cascade is activated by endogenous inflammatory agents, such as undigested DNA (49,50) and the neuro-peptide bursicon (51), as well as undefined humoral factors released from the intestine after tissue damage (52). The observation of different signaling pathways that are activated in response to various forms of stress, and in the dronc mutant, indicate that specific detection mechanisms are used to discriminate among various forms of threat.…”
Section: Discussionsupporting
confidence: 52%
“…The induction of gut immune-signaling pathways likely results from recognition of parasite-associated molecular patterns by the gut epithelia. Immune molecules produced by the gut epithelia, such as reactive oxygen species (19) or cardia-produced inducible nitric oxide (iNOS) (20), may further lead to systemic immune induction in other organs (21). Our previous study that investigated fat body responses in adult flies noted strong induction of the Imd pathway and one of its effector products (antimicrobial peptide Attacin-A) 72 h after exposure to trypanosomes (14).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by analogy to Drosophila, other cellular and humoral responses that may also involve the fat body are likely to influence oocyst survival. In Drosophila, hemocytes are key intermediate components required for interorgan communication between the midgut and fat body and are required for activation of humoral immunity and pathogen elimination (36,37).…”
Section: Discussionmentioning
confidence: 99%